Correlation between Inter-Blink Interval and Episodic Encoding during Movie Watching. - Young Seok Shin; Won-du Chang; Jinsick Park; Chang-Hwan Im; Sang In Lee; In Young Kim; Dong Pyo Jang (PLoS ONE, 2015)
Human eye blinking is cognitively suppressed to minimize loss of visual information for important real-world events. Despite the relationship between eye blinking and cognitive state, the effect of eye blinks on cognition in real-world environments has received limited research attention. In this study, we focused on the temporal pattern of inter-eye blink interval (IEBI) during movie watching and investigated its relationship with episodic memory. As a control condition, 24 healthy subjects watched a nature documentary that lacked a specific story line while electroencephalography was performed. Immediately after viewing the movie, the subjects were asked to report its most memorable scene. Four weeks later, subjects were asked to score 32 randomly selected scenes from the movie, based on how much they were able to remember and describe. The results showed that the average IEBI was significantly longer during the movie than in the control condition. In addition, the significant increase in IEBI when watching a movie coincided with the most memorable scenes of the movie. The results suggested that the interesting episodic narrative of the movie attracted the subjects' visual attention relative to the documentary clip that did not have a story line. In the episodic memory test executed four weeks later, memory performance was significantly positively correlated with IEBI (p<0.001). In summary, IEBI may be a reliable bio-marker of the degree of concentration on naturalistic content that requires visual attention, such as a movie.